ANALYSIS OF SERVANT AND TRANSFORMATIONAL LEADERSHIP ON CORPORATE SOCIAL REPONSIBILITY AT GEREJA KALVARI PENTAKOSTA MISSI DI INDONESIA - Rau, Theodorus Vincent; Saerang, David P.E; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Servant leadership and Transformational leadership are a leadership styles that must be owned by the present leaders. In this study, leadership style (servant leadership and transformational leadership) become the keys for investigating the corporate social responsibility in church. The aim is to examine the impact servant leadership and transformational leadership for the succeed of corporate social responsibility. The population of this research is all pastors of GKPMI. And the sample is 8 pastors from this church. This research used qualitative analysis, using the interview and observation techniques. This research found that servant leadership and transformational leadership must run together to obtain the corporate social responsibility, and it compliment and balanced the CSR in organization. Because it mixed together, the CSR is higher than before. Conclusion Servant leadership and transformational leadership have a positive impact toward congregation and because of that the corporate social responsibility in this organization is good enough, or can say extremely well. Recommendation for the church is to apply this servant and transformational leadership so the church can manage the CSR well. Keywords: servant, transformational leadership, corporate social responsibility